Design, Synthesis, and Development of Novel Fluorescently Labelled Allosteric Probes for the Human Beta2-Adrenoceptor - Tuzer, Cemre (2023)
It has started to be questioned that the success rate of traditional G protein-coupled receptor (GPCR)-based drug discovery is in decline related to the difficulty in selectively targeting the orthosteric binding site at receptors that display high sequence homology between subtypes. In the last decade, small molecules that target topographically distinct allosteric sites on GPCRs have shown great success and offer enormous potential in terms of achieving higher selectivity, fewer side effects, and lower toxicity. Allosterism in drug discovery has, therefore, emerged as a promising strategy to develop efficient and safe therapeutics. Since the selectivity of current clinically available ß-blockers is still poor, attaining selectivity via targeting potential allosteric pockets on the ß-adrenoceptors (ßAR), could help meet this clinical need. An early development in this approach is shown by a molecule termed Cmpd15, which has been reported as a negative allosteric modulator of the ß2AR. Additional compounds have further informed current studies at the ß2AR, such as Cmpd6, a positive allosteric modulator, and AS408, a negative allosteric modulator. In the current study, previously reported ß2AR allosteric modulators Cmpd6 and Cmpd15 have been re-synthesised. Pharmacological characterisation of these compounds in respect to the nature of their allostery was determined using bioluminescence resonance energy transfer (BRET) technology as well as functional assays such as CRE-SPAP reporter and GloSensor cAMP accumulation assays. We also report the physical approaches and chemical routes for the separation and chiral synthesis of R- and S-Cmpd15 in order to compare their in vitro activity with the corresponding racemic mixture. Additional studies also describe the development of novel fluorescently labelled 2AR allosteric fluorescent ligands. Evaluation of the existing SAR studies of Cmpd6 informed the selection and location of the linker-fluorophore conjugation. Coupling of an optimised linker and a red- emitting fluorophore (BODIPY 630/650-X) with Cmpd6 generated the first synthetic allosteric fluorescent ligandCmpd6BODIPY-630/650-X for ß2AR. Assessment of the binding affinity of the fluorescent ligand was achieved via NanoBRET saturation binding assays, which showed agreeable affinity in comparison to the parent compound. This newly synthesised fluorescent ligand was further employed as a robust allosteric screening tool and has allowed the identification of new hit fragments for the proposed allosteric binding site of Cmpd6.